2021
DOI: 10.3390/axioms10010025
|View full text |Cite
|
Sign up to set email alerts
|

A New Inverted Topp-Leone Distribution: Applications to the COVID-19 Mortality Rate in Two Different Countries

Abstract: This paper aims to find a statistical model for the COVID-19 spread in the United Kingdom and Canada. We used an efficient and superior model for fitting the COVID 19 mortality rates in these countries by specifying an optimal statistical model. A new lifetime distribution with two-parameter is introduced by a combination of inverted Topp-Leone distribution and modified Kies family to produce the modified Kies inverted Topp-Leone (MKITL) distribution, which covers a lot of application that both the traditional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 27 publications
0
26
0
Order By: Relevance
“…10 Almetwally et al(71) The authors suggested a model for fitting the COVID 19 mortality rates in the UK and Canada using optimal statistical technique. They have suggested a new two-parameter lifetime distribution by combining inverted Topp-Leone (ITL) and modified Kies inverted Topp-Leone (MKITL) distributions.…”
mentioning
confidence: 99%
“…10 Almetwally et al(71) The authors suggested a model for fitting the COVID 19 mortality rates in the UK and Canada using optimal statistical technique. They have suggested a new two-parameter lifetime distribution by combining inverted Topp-Leone (ITL) and modified Kies inverted Topp-Leone (MKITL) distributions.…”
mentioning
confidence: 99%
“…These data set up of disaster mortality rate. In addition, we notice that Almetwally et al [25] analyzed this dataset to demonstrate the suitability of the new inverted Topp-Leone model. The next set of data is a 30-days COVID-19 data set from the Netherlands, and is obtained between March 31 and April 30, 2020.…”
Section: Real Data Applicationsmentioning
confidence: 81%
“…The MKIF model's potentiality for two real datasets is demonstrated in this section. MKIF distribution is collated with other reasonable models, namely: modified Kies inverted Topp-Leone (MKITL) distribution [25] , modified Kies exponential (MKEx) [26] , and Fréchet distribution. Some goodness-of-fit measures are used to compare the fitted distributions, including the Akaike Information (AIC), Bayesian Information (BIC), CAIC (consistent Akaike information) and HQIC (Hannan-Quinn information) criterions.…”
Section: Real Data Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These estimation methods would be of particular interest when comparing them with other maximum likelihood estimation procedures. For more examples of classical estimation method, see the works of Almetwally [ 25 ], El-Morshedy et al [ 26 ], Almetwally et al [ 27 ], and Sabry et al [ 28 ].…”
Section: Different Estimation Methodsmentioning
confidence: 99%